The Learning Behaviour Based on Islamic Value; Strategy Improvement for Pesantren Sustainability - Khoirunnisak, Khoirunnisak; Abdullah, Abdullah; Mudarris, Badrul; Maiyeenah Pochiseng (Al-Qalam Institue, 2023)
This research aims to explore the influence of Islamic values on the learning behaviour of students in Islamic boarding schools, as well as designing educational improvement strategies to increase the sustainability of Islamic boarding schools in achieving the goals of holistic Islamic education. The research method used is a qualitative approach with a descriptive type. Data collection techniques involve observation, interviews, and documentation. Data analysis was carried out in three stages, namely data condensation, data exposure, and concluding with verification. The research results show that implementing the right strategy can improve the quality of Islamic boarding school education and maintain the sustainability of these institutions in the global era. Strategy improvements include improving the quality of teaching with relevant methods, diversifying the curriculum according to global demands, effective financial management, community participation in financial support and Islamic boarding school facilities, developing human resources through continuous training, utilizing information technology, and preparing long-term strategic plans.